Effects of geometer's sketchpad on students' achievement of combined transformations and attitude towards mathematics - Suraini, binti Haji Bujang (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This study examined the effects of using Geometer's Sketchpad (GSP) on students' representation, understanding and achievement of combined transformations. It further investigated the main and interactions effects of gender, treatment types and ability level on the scores on the Transformation Achievement Test and Aiken's Mathematics Attitude Scale.